"I've Got News for You": Life Themes and the Therapeutic Relationship. Issue 1 (2nd January 2017) - Jaenicke, Chris
Abstract : The gap between our theoretical explanations and our phenomenological descriptions in therapeutic processes is discussed. The failure to acknowledge the extent of our involvement is to be found and explained in the nature of the relationship between the bi-directional and the asymmetric levels of discourse in psychotherapy. The bi-directional level of psychotherapy consists of working through the encounter of the two subjectivities involved. The life themes of both the patient and the analyst are seen to be negotiated on the bi-directional level of the interchange, while the asymmetric level of discourse is seen to guarantee the safety and the purpose of therapy. Similarities and differences in the relational and intersubjectivist view of the level of mutual influencing are discussed. A claim is made that the extent of the influence of the therapist's subjectivity in regard to what is being treated has not been acknowledged and necessitates a much higher degree of awareness that the wellspring of any therapeutic encounter will be the working-through of the life themes of both participants. A case example is given to illustrate these theses.